COMMUNITY EMPOWERMENT IN ORGANIC WASTE MANAGEMENT IN THE BATUMADEG AND BATUKANDIK VILLAGE TOURIST AREA, NUSA PENIDA, BALI - Wihardyanto, Dimas; Umi Latifah, Nadia Nurlaili; Widiastuti, Kurnia; Fania, Siti Nayla; Khoirunnisa, Salsabila (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2025)
Waste management in the Nusa Penida tourism area, Bali Province, is a major concern in maintaining environmental and tourism sustainability. Serious problems related to waste management in the Bali region, especially Nusa Penida, inspired the Gadjah Mada University (UGM) Period 2 Nirwana KKN Team to carry out activities to empower the public. Through qualitative methods using Forum Group Discussions (FGD) and interviews, the KKN Team succeeded in identifying multidimensional waste problems, including cultural and structural dimensions in the region. Therefore, in formulating solutions, the focus should not only be on improving facilities, but also on increasing public awareness as a whole. And it is best if the initiation that is designed is bottom-up and prioritizing audiences from community groups. In this regard, the KKN Team developed a four-step solution, which includes education on waste sorting, a TOSS (Local Waste Processing Site) survey, introduction of eco-enzymes from organic waste, and the creation of the tools named Holzewiq to process plastic waste. Significant results can be seen in increasing public awareness regarding waste issues, fulfilling community aspirations regarding waste management facilities, and the effectiveness of TOSS. The Eco-Enzyme program and the Holzewiq tool also produce positive public response. The KKN team succeeded in processing 5 kg of inorganic waste into sustainable products. With active community participation, this project makes a real contribution to waste management and has the potential to create continuity in the long term.